Kualiti kerja dalam organisasi: tinjauan dari perspektif pengurusan Islam - Masitah Idris,; Wan Fariza Alyati Wan Zakaria,; Ahmad Sunawari Long,; Nozira Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Management is a tool to improve quality of work and its relationship with the success of organisation therefore very fundamental. It begins with the power system, process of planning, prosedure and rules which can provide excellent contribution to the organization. This article will discuss some basic principle of management to improve the quality of work performance according to Islamic perspective. These fundamental principles include values such as insaniyyah (humanity), tawhīd (unity), shūra (consultation) and istiqamah (steadfastness) in every action. It emphasises on attaining spiritual success through deligence in work of excellence. It means to get the best quality of work through both spiritual and material satisfaction whether by the employer and also the employee. This paper also discusses other elements that contribute to improve quality of work in Islamic perspective in order to achieve organisational success such as al-niyyah (having purpose), amanah (integrity), time management, cadl (justice/balance) and tacāwun (cooperation). Highly committed employee who combined all these elements will make great contribution to the organisation. Therefore, it is significant to stress the relevant relationship between all elements with quality of work within the Islamic perspective. Some elements which differentiates Islamic management with conventional management in general were also discussed in comparative manner to highlight the benefits of Islamic management to the overall well being of the employer and the employee as well as the organisation as a whole.